Predictive Factors of the Standard Cross-linking Outcomes in Adult Keratoconus: One-Year Follow-Up - Amani E. Badawi; Waleed Ali Abou Samra; Ayman Abd El ghafar (Journal of Ophthalmology)
Purpose. To evaluate the effects of preoperative presumed predictor factors on clinical and topographic outcomes in adult keratoconus (KC) 1 year after the standard corneal cross-linking (CXL). Design. Retrospective cohort study. Methods. The study included 84 KC patients (136 eyes) who were treated with conventional CXL. Postoperative best-corrected visual acuity (BCVA) and K max were considered the main predicted variables. The entire participants were divided into subgroups with cutoff values in accordance with the predictive variables. The predicted postoperative outcomes at one year were compared between the subgroups. Next, the predictive variables were analyzed by univariate and multivariate linear regression. Results. In respect to the BCVA, univariate analysis showed that the worse BCVA, the higher K max, and the relative thinner corneas were relatively good predictors of improvement, while multivariate evaluation revealed a strong interrelation with preoperative BCVA only. Regarding the postoperative flattening, univariate analysis found that the cone location and worse preoperative BCVA were the pronounced predictors, whereas the multivariate evaluation focused on the impact of the cone location only. Conclusions. The multivariate analysis disclosed a significant negative association between the baseline BCVA and postoperative BCVA and a positive relationship between the cone eccentricity and postoperative K max.